Drug‐induced liver injury in the era of biologics: The case of natalizumab. Issue 3 (16th March 2021) - Taveira, Filipe; Lopes, Sandra; Faria, Carlos; Mendes, Sofia; Figueiredo, Pedro
Abstract: Drug‐induced liver injury (DILI) is a challenging diagnosis regarding the complexity of mechanisms, drugs, supplements, and herbs that can have hepatotoxic potential. Biologics are increasing as common drugs in the treatment of chronic inflammatory diseases and some DILI were previously reported with those agents. Natalizumab, a recombinant monoclonal antibody used for the treatment of multiple sclerosis (MS) has a good safety profile with extremely rare liver‐related adverse events. The clinical case of a 44‐year‐old female with the history of MS and the recent start of natalizumab was reported. The patient was admitted with jaundice, choluria, fatigue, anorexia, nausea, and diffuse abdominal discomfort. No signs of encephalopathy or MS flare on examination. Laboratory values: aspartate aminotransferase, 905 U/L; alanine transaminase, 1559 U/L; ALP, 127 U/L; GGT, 301 U/L; total bilirubin, 12.8 mg/dL; direct bilirubin, 5.9 mg/dL, Albumin 2.9 g/dL, platelet 137 g/L, and 2.44 INR. No infectious, vascular, metabolic causes, or biliary obstruction were found. Liver biopsy suggested toxic hepatitis with autoimmune features. Since no definite criteria for autoimmune hepatitis (AH) were met, steroids were not given. The patient was on supportive measures and was presented to a liver transplant unit. Therefore, DILI due to natalizumab was assumed and its discontinuation led to the resolution of all symptoms in a 6‐month window. The increasingly common use of biological therapy or with direct influence on the immune system should raise the suspicion of the gastroenterologist in all cases of suspected DILI.